2007
DOI: 10.2165/00063030-200721050-00004
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Conditioned Serum in the Treatment??of Orthopedic Diseases

Abstract: The common strategies for the treatment of patients with orthopedic diseases do not address the underlying pathogenesis. Several biologically based, local therapies aiming to influence the cytokine imbalance are either in development or in the initial stages of clinical use. A method based on exposure of blood leukocytes to pyrogen-free surfaces (e.g. glass spheres) elicits an accumulation of anti-inflammatory cytokines, including interleukin-1 receptor antagonist, and several growth factors, including insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(185 citation statements)
references
References 5 publications
7
157
1
7
Order By: Relevance
“…[26][27][28] Autologous serum has been used over the last two decades to promote the healing of epithelial and cartilaginous damage of both known and unknown aetiologies. 13,[29][30][31] At the same time, it includes various immunoglobulins (e.g. immunoglobulin G and immunoglobulin A) and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Autologous serum has been used over the last two decades to promote the healing of epithelial and cartilaginous damage of both known and unknown aetiologies. 13,[29][30][31] At the same time, it includes various immunoglobulins (e.g. immunoglobulin G and immunoglobulin A) and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, healing factors such as nerve growth factor, epidermal growth factor, transforming growth factor β, platelet-derived growth factors and insulin-like growth factor-1 are present in both diluted and undiluted serum. 9 Nerve growth factor is the bestknown neurotrophic factor; it is responsible for the growth and survival of developing neurons, and the maintenance of mature neurons. 10,11 Recent studies have indicated the efficacy of autologous serum in the treatment of neurotrophic keratopathy, osteoarthritis, chronic graft-versus-host disease and tympanic membrane perforations.…”
Section: Introductionmentioning
confidence: 99%
“…Orthokine is now available in the USA as Regenokine; however, independent publications of clinical results have not been reported from this experience. Orthokine/Regenokine is autologous conditioned serum (ACS), which is procured from autologous blood that is incubated with borosilicate glass spheres, leading to increased levels of IL-1 receptor antagonist (IL-1ra) [50]. An equine model of induced OA demonstrated no adverse events along with improvements in lameness and histology compared to the placebo group [51].…”
Section: Growth Factor Treatmentsmentioning
confidence: 99%
“…Meijer et al (2003) desenvolveram o ACS comercial rico em proteína antagonista do receptor de interleucina -1 (IL-1ra) a partir da coleta asséptica de sangue venoso. Recentemente, estudos demostraram que o ACS também possui fatores de crescimento (WEHLING et al, 2007;HRAHA et al, 2011), mudando o conceito acima relatado.…”
Section: Derivados Sanguíneosunclassified
“…Assim, o ACS, sob os nomes comerciais de Irap® e Irap II®, para uso veterinário, e Orthokine® para uso humano, é um derivado sanguíneo rico em IL1ra, possuindo também em sua constituição alguns fatores de crescimento, como fator de crescimento fibroblástico-1 (FGF-1), fator de crescimento do hepatócito (HGF), fator de crescimento transformante-β1 (TGF-β1) , fator de crescimento tipo insulina-1 (IGF-1) e fator de crescimento derivado de plaquetas (PDGF) (WEHLING et al, 2007), além de citocinas antiinflamatórias como as interleucinas-10 e -4 (IL-10, IL-4) (MEIJER et al, 2003).…”
Section: Derivados Sanguíneosunclassified